2018
DOI: 10.1007/s10705-018-9956-0
|View full text |Cite
|
Sign up to set email alerts
|

Critical plant and soil phosphorus for wheat, maize, and rapeseed after 44 years of P fertilization

Abstract: Phosphorus (P) crop fertilization requires optimal management to avoid the waste of a nonrenewable resource and water pollution, but current methods for assessing soil phyto-available P and plant P requirements are not sufficiently precise to meet this goal. The objectives of the present study were to (1) evaluate the effect of long-term P fertilization on the grain yield of winter wheat, maize, and rapeseed, (2) validate or establish models of critical shoot P concentration (P C ) based on relationships of sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 45 publications
3
30
6
Order By: Relevance
“…The overall dilution rate of N in our study (b = 0.23, on average of four treatments) was about half of the b value (b = 0.44) from the critical dilution curve proposed by Justes et al (1994). While for P, our values were above the values proposed by Cadot et al (2018) (0.09 as compared to 0.04), and for S, the IM system was below that suggested by Reussi et al (2012) (0.13 as compared to 0.17) (Supplemental Table S4).…”
Section: Treatment Impacts On Nutrient Dilution Curve Of N P K and Scontrasting
confidence: 53%
“…The overall dilution rate of N in our study (b = 0.23, on average of four treatments) was about half of the b value (b = 0.44) from the critical dilution curve proposed by Justes et al (1994). While for P, our values were above the values proposed by Cadot et al (2018) (0.09 as compared to 0.04), and for S, the IM system was below that suggested by Reussi et al (2012) (0.13 as compared to 0.17) (Supplemental Table S4).…”
Section: Treatment Impacts On Nutrient Dilution Curve Of N P K and Scontrasting
confidence: 53%
“…Compared with the NF and MN treatments, the extraction e ciencies and concentrations were higher in the P-fertilized treatments (NP and MNP) at different depths, which is consistent with the literature (Table 1; Xin et al, 2019). Our results are also consistent with the ndings of Cadot (2018) who reported that fertilization can signi cantly increase the number of results per corn plant and the weight of stems and leaves (Table 2). In the current study, higher plant height and thicker stem diameter were found after the manure fertilizer treatments (MN, MNP), but there was no signi cant difference between the unfertilized and mineral fertilizer (NF, NP) soils, which is inconsistent with previous research suggesting that fertilizer application increases the height and stem of plants (Jiang et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…The one exception to the growth rate hypothesis was represented by the stoichiometry of P. sativum that, in sandy soil, was characterized by higher biomass C:P ratio and, although not significant, higher biomass N:P ratio notwithstanding a higher productivity (Table 1, Table S4). A possible explanation is that P stoichiometry of P. sativum was more affected by the dilution effect associated to a higher productivity (Cadot et al 2018). This is in line with the higher P concentration of P. sativum in clay soil where, notwithstanding a lower P availability (P m i n ) (Table S1), the biomass productivity was significantly lower (Table S4).…”
Section: General Pattern Of Plant and Microbial Stoichiometrymentioning
confidence: 52%